Effect of shading on physiological attributes and comparative transcriptome analysis of Camellia sinensis cultivar reveals tolerance mechanisms to low temperatures - Zaman, Shah; Shen, Jiazhi; Wang, Shuangshuang; Song, Dapeng; Wang, Hui; Ding, Shibo; Pang, Xu; Wang, Mengqi; Sabir, Irfan Ali; Wang, Yu; Ding, Zhaotang (Frontiers in Plant Science, 2023)
Tea is a vital beverage crop worldwide, including China. Low temperatures harshly restrict its growth, development, and terrestrial spread, and fluctuation in cold events increases cold-damage injury. However, the physiological and molecular mechanism of (Camellia sinensis L.) under shading in winter remains elusive. In the present study, tea leaves were used for physiological attributes and transcriptomic analysis under three shading and no-shade control plants in November and December during low temperature. Shading group protected tea leaves from cold damage and intensified photochemical efficiency (Fv/Fm), Soil Plant Development Analysis (SPAD), and optimized chlorophyll a and b, chlorophyll, and carotenoid contents compared to no-shade control plants. For transcriptomic analysis, 20807 genes (DEGs) were identified respectively. Comparative statistical analysis revealed 3523 DEGs and several transcription factors (TF) under SD0% vs. SD30%, SD0% vs. SD60%, and SD0% vs. SD75% of shade in November and December during low temperature. Interestingly, the number of down-regulated DEGs were higher than that of up-regulated DEGs. Indicates that cold temperature affected the numbers of DEGs and transcriptional factors under three shading groups compared with no-shade control plants during low temperature. Further analysis indicated that low temperatures activated the essential DEGs and transcription factors in Photosynthesis, Plant hormone signal transduction, and MAPK signaling pathways. The increased expression of key DEGs light harvesting photosystem I gene Lhca5, and light harvesting in photosystem II gene Lhcb2 and the higher expression of mitogen-activated protein kinase MEKK1 and MPK4/6 enhance the cold-tolerance mechanism in (Camellia sinensis L.). In our findings, low temperature activates cold cascades, transmits prominent signaling events in the nucleus, and might sustain the membrane fluidity under shade and no-shade control plants. More DEGs and transcription factors were triggered in the extreme cold during December compared to November. Indicates that shading protects tea leaves from severe cold injury, restricts ice accumulation and increases the cold-tolerance mechanism of (Camellia sinensis L.). Our findings lead to future studies aimed at understanding the complex molecular mechanisms by which tea plants survive during low temperature.